Faktor Penentu Perencanaan Keuangan Keluarga Islami - Yuliansyah; Achmad Firdaus; Saiful Anwar (Department Islamic Economics, 2023)
This study aims to analyze the determinants of Islamic family financial planning. In this case, psychological factors, sociological factors, financial factors and religiosity factors influence the decision to have financial planning. This study uses descriptive quantitative methods with a causal research design. Methods of data analysis in research using Component or Variance Based Structural Equation Modeling which in data processing using the Partial Least Square (Smart-PLS) program. Respondents in this study were 252 people who were over 35-45 years old, Muslim, who were in the Jakarta and Tangerang areas. The results of the study found that psychological factors did not influence respondents to carry out financial planning. In this study, it was also found that religiosity factors had a negative and significant effect on respondents in financial planning. Social and financial factors influence respondents in financial planning positively and significantly.